Incidence and In‐Hospital Mortality of Acute Kidney Injury (AKI) and Dialysis‐Requiring AKI (AKI‐D) After Cardiac Catheterization in the National Inpatient Sample. Issue 3 (15th March 2016) - Brown, Jeremiah R.; Rezaee, Michael E.; Nichols, Elizabeth L.; Marshall, Emily J.; Siew, Edward D.; Matheny, Michael E.
Abstract : Background: Acute kidney injury (AKI) and dialysis‐requiring AKI (AKI‐D) are common, serious complications of cardiac procedures. Methods and Results: We evaluated 3 633 762 (17 765 214 weighted population) cardiac catheterization or percutaneous coronary intervention (PCI) hospital discharges from the nationally representative National Inpatient Sample to determine annual population incidence rates for AKI and AKI‐D in the United States from 2001 to 2011. Odds ratios for both conditions and associated in‐hospital mortality were calculated for each year in the study period using multiple logistic regression. The number of cardiac catheterization or PCI cases resulting in AKI rose almost 3‐fold from 2001 to 2011. The adjusted odds of AKI and AKI‐D per year among cardiac catheterization and PCI patients were 1.11 (95% CI: 1.10–1.12) and 1.01 (95% CI: 0.99–1.02), respectively. Most importantly, in‐hospital mortality significantly decreased from 2001 to 2011 for AKI (19.6–9.2%) and AKI‐D (28.3–19.9%), whereas odds of associated in‐hospital mortality were 0.50 (95% CI: 0.45–0.56) and 0.70 (95% CI: 0.55–0.93) in 2011 versus 2001, respectively. The population‐attributable risk of mortality for AKI and AKI‐D was 25.8% and 3.8% in 2001 and 41.1% and 6.5% in 2011, respectively. Males and females had similar patterns of AKI increase, although males outpaced females. Conclusions: The Incidence of AKI among cardiac catheterization and PCI patients has increased sharply in the United States, and this should be addressed by implementing prevention strategies. However, mortality has significantly declined, suggesting that efforts to manage AKI and AKI‐D after cardiac catheterization and PCI have reduced mortality.